Discovery of a Novel Variant of SEMA3A in a Chinese Patient with Isolated Hypogonadotropic Hypogonadism - Wenting Dai; Jia-Da Li; Xinying Wang; Wang Zeng; Fang Jiang; Ruizhi Zheng (International Journal of Endocrinology)
Semaphorin (SEMA) has an important role in nerve development, organ formation, immune response, angiogenesis, and tumor growth. SEMA can regulate the growth and branching of axons, the morphology of dendrites, and the migration of neurons. The loss-of-function in SEMA and its receptors PLXNs and NRP affect the migration of GnRH neurons, leading to idiopathic hypogonadotropic hypogonadism (IHH). As a member of the SEMA family, SEMA3A has an important role in axonal rejection, dendritic branching, synaptic formation, and neuronal migration. There are more and more SEMA3A variants identified in IHH patients. In this study, we identified a novel SEMA3A variant (c.1369A > G (p.T457A)) in a male nIHH patient. Functional studies indicated that the T457A SEMA3A variant led to the defect of FAK phosphorylation and GN11 cell migration, which strongly argued in favor of its pathogenic effect in the nIHH patient. Our findings substantiated that the 435–457 position of SEMA3A might be very important for the secretion of SEMA3A. Haploin-sufficiency of SEMA3A in humans was sufficient to cause the IHH phenotype. SEMA3A variants might have a role in modifying the IHH phenotype, according to the variants at different positions of SEMA3A. SEMAs and its receptors formed a complex network, and other members of the SEMA-signaling pathway might also be involved in the pathogenesis of IHH.